Evaluation of Prevalence and Risk Factors for Postpartum Depression Using the Edinburgh Postpartum Depression Scale: A Cross-Sectional Analytic Study - Gaye Kahveci; Bekir Kahveci; Hamza Aslanhan; Pakize Gamze Erten Bucaktepe (Gynecology Obstetrics & Reproductive Medicine)
Objective: To evaluate the prevalence and associated risk factors for postpartum depression (PPD) using the Edinburgh Postpartum Depression Scale (EPDS).